2019
DOI: 10.1002/oby.22511
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Scoping Review of Surgically Manipulated Adipose Tissue and the Regulation of Energetics and Body Fat in Animals

Abstract: Objective Surgical manipulations of adipose tissue by removal, or partial lipectomy, have demonstrated body fat compensation and recovered body weight, suggesting that the body is able to resist changes to body composition. However, the mechanisms underlying these observations are not well understood. The purpose of this scoping review is to provide an update on what is currently known about the regulation of energetics and body fat after surgical manipulations of adipose tissue in small mammals. Methods PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(407 reference statements)
0
4
0
Order By: Relevance
“…In this section, we examine the effects of fat removal on metabolism and body weight control. In rodent models of SAT or VAT removal, there is a tendency for weight regain, which may lead to loss of any metabolic effects [ 60 ]. The lipectomy reports we identified did not report on changes in liver size, fatty liver, or other markers of ectopic lipid distribution.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we examine the effects of fat removal on metabolism and body weight control. In rodent models of SAT or VAT removal, there is a tendency for weight regain, which may lead to loss of any metabolic effects [ 60 ]. The lipectomy reports we identified did not report on changes in liver size, fatty liver, or other markers of ectopic lipid distribution.…”
Section: Resultsmentioning
confidence: 99%
“…There is some debate as to whether lipectomy itself is ineffective, or whether there is an underlying problem of energy imbalance that has not been corrected. Despite the variable results obtained after lipectomy, most experimental studies demonstrated body fat compensation and weight recovery, suggesting that biological feedback mechanisms act to resist long-term changes in body weight/fat [ 46 ]. This is because the body aims to maintain an energy balance that requires a complex integration of energy stores, energy expenditure, and energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that rodent models of fat biology do not adequately represent what happens in humans, and higher mammals such as baboons may be a better model that closely resembles human adipocyte function [87]. Thus far, results from studies designed to identify the factors that address the regulation of energetics and body fat redistribution/ regeneration post-SSFR in rats, mice or hamsters have limited contribution in closing the knowledge gap because of insufficient mechanistic data, inadequate sample size, or lack of proper statistical tests reported [88]. Therefore, future studies in appropriate animal models or human clinical trials should account for the biological consequences of ectopic fat redistribution following weight gain post-SSFR.…”
Section: Other Considerations and Future Tasksmentioning
confidence: 99%